Prioritas Pengembangan Kompetensi Green Job pada Industri Konstruksi Menggunakan Importance-Performance Analysis - Hadi, Patria Yoga Pratama; Soetjipto, Jojok Widodo; Wiswamitra, Ketut Aswatama (JURNAL TEKNIK SIPIL, 2025)
The implementation of green building construction in Indonesia is still limited, despite the increasing environmental damage caused by the conventional construction industry. The government has issued several regulations on green buildings and sustainable construction, but implementation is still not optimal. Furthermore, the concept of Green Jobs, as jobs that contribute to preserving or restoring environmental quality, is not yet widely recognized by construction service providers in Indonesia. In fact, a workforce with sustainable development knowledge and skills is crucial to support environmentally friendly construction practices. This study aims to evaluate the importance and application of green construction principles in the construction sector and determine priority actions. The research method used is Importance Performance Analysis (IPA), which involves administering questionnaires to construction stakeholders. This study is expected to provide a basis for formulating policies for developing Green Jobs by improving the competency of human resources for sustainable development. The results indicate a gap between high importance and low performance, with three important areas as the main priorities: mastery of green building technology, Zero Energy/Low Emission Building Systems, and Building Information Modeling (BIM) for sustainability. Proposed strategies include certified training, integrating sustainability criteria into procurement, and encouraging public-private partnerships for technology transfer. These findings provide a roadmap for all industry stakeholders to accelerate the development of a sustainable construction-skilled workforce.